Is Longer Maternal Care Always Beneficial? The Impact of a Four-Year Paid Parental Leave - Alena Bicakova; Klara Kaliskova (Institute of Labor Economics (IZA), 2022)
We study the impact of an extension of paid family leave from 3 to 4 years on child long- term outcomes. Using a difference-in-differences design and comparing the first-affected with the last-unaffected cohorts of children, we find that an additional year of maternal care at the age of 3, which primarily crowded out enrollment into public kindergartens, had an adverse effect for children of low-educated mothers on human capital investments and labor-market attachment in early adulthood. The affected children were 12 p.p. more likely not to be in education, employment, or training (NEET) at the age of 21-22. The impact on daughters was larger and driven by a lower probability of attending college and higher probability of home production. Sons of low-educated mothers, on the other hand, were less likely to be employed. The results suggest that exposure to formal childcare may be more beneficial than all-day maternal care at the age of 3, especially for children with a lower socio-economic background.
Keywords: J13; J18; J21; J24; 330; family leave; maternal care; subsidized childcare; child outcomes; human capital; labor-market attachment